Penguatan Pengetahuan dan Kesadaran Masyarakat dalam Upaya Pencegahan Stunting melalui Edukasi Kesehatan - Achmad Djunawan; M Risya Rizki; Emilia Indahyati; Puriyanti Puriyanti; Antika Silva Patricia Wandira; Jihan Lailatus Shibyana C N; Nurul Isnainil Muhammadah (STIKES Yayasan RS.Dr.Soetomo, 2026)
Stunting remains a major public health problem in Indonesia. It is close associate to inadequate maternal nutrition, limited health knowledge, and low community awareness. Community-based health education has a crucial role in evaluating these factors by empowering families and high-risk groups. This community service aims to improve knowledge and self-awareness related to stunting prevention among mothers with children. This community empowerment is implemented using structured health education sessions, interactive discussions, practical demonstrations, and learning modules. Activities are conducted in several stages, including preparation, implementation, and evaluation. Knowledge improvement assessment using a pre-test and post-test approach. It is compare participant’s scores before and after the intervention. The findings show that participants’ understanding of stunting, its risk factors, and the importance of maternal and child nutrition increases. Participants demonstrate improved awareness of growth monitoring and preventive practices following the educational intervention. The community service program effectively enhanced knowledge and awareness related to stunting prevention. These results highlight the potential of structured educational approaches as sustainable strategies to support early stunting prevention at the community level.